Tax Fraud and Tax Education in Spain - Durán-Sindreu Buxadé, Antonio (2014)
The main cause of tax fraud in Spain is, in author’s opinion, the educational deficits as individuals. Taxes are not to be just an obligation, he points, but contributing to a morefair society, convinced that requires, as in other areas, a thorough reform of the educationsystem and the recovery of traditional values that our society is suffering a deep crisis. In thissense, the author thinks we must link the estate fraud to educational and cultural deficitsthat Spain suffers, since the crisis of values is what underlies most cases of tax or offenses, ifpreferred, to conduct contrary to law or, without more, antisocial. In this context, the authorindicates it is essential also internalize the culture of spending, since everything is funded by our taxes.